2016
DOI: 10.1007/s12079-016-0359-1
|View full text |Cite
|
Sign up to set email alerts
|

CCN2 induces cellular senescence in fibroblasts

Abstract: The expression of Ccn2 (CTGF) has been linked to fibrosis in many tissues and pathologies, although its activities in fibroblastic cells and precise mechanism of action in fibrogenesis are still controversial. Here, we showed that CCN2 can induce cellular senescence in fibroblasts both in vitro and in vivo, whereupon senescent cells express an anti-fibrotic Bsenescence-associated secretory phenotype( SASP) that includes upregulation of matrix metalloproteinases and downregulation of collagen. Mechanistically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 43 publications
1
43
1
1
Order By: Relevance
“…The expression of CDKN2B was significantly enhanced in tumors from mice treated with ETC-159 alone and further increased in tumors treated with the combination containing olaparib ( Figure 6C). In addition, expression of the senescence markers IL32 and CCN2 and protein levels of p21 (53)(54)(55) were also higher in the tumors from the ETC-159 and olaparib combination group compared to the tumors treated with ETC-159 or olaparib alone (Figures 6C-D). Loss of LMNB1 (lamin B1) is also associated with senescence (56, 57) and we observed a marked reduction in its expression in the tumors treated with ETC-159 either alone or in combination with olaparib ( Figure 6E).…”
Section: Olaparib and Etc--159 Combination Enhances Senescencementioning
confidence: 92%
“…The expression of CDKN2B was significantly enhanced in tumors from mice treated with ETC-159 alone and further increased in tumors treated with the combination containing olaparib ( Figure 6C). In addition, expression of the senescence markers IL32 and CCN2 and protein levels of p21 (53)(54)(55) were also higher in the tumors from the ETC-159 and olaparib combination group compared to the tumors treated with ETC-159 or olaparib alone (Figures 6C-D). Loss of LMNB1 (lamin B1) is also associated with senescence (56, 57) and we observed a marked reduction in its expression in the tumors treated with ETC-159 either alone or in combination with olaparib ( Figure 6E).…”
Section: Olaparib and Etc--159 Combination Enhances Senescencementioning
confidence: 92%
“…3.2 | CCN2 increases ABCG2 expression via the α6β1 integrin receptor in human osteosarcoma cells CCN2 is capable of binding various growth factors or integrins and modifying their activity in certain carcinoma cells (Jun & Lau, 2017;Yang et al, 2016;Zeng et al, 2017). The most researched CCNbinding receptors are the integrins αvβ3, αvβ5, α5β1, and α6β1 (Lau, 2016).…”
Section: Ccn2 Enhances Abcg2 Expression and Increases Osteosarcoma mentioning
confidence: 99%
“…Upregulation of Ccn1 was vitally important to prevent excessive fibrosis. More recently, the same authors demonstrated that topical application of another Ccn family member, Ccn2, similarly actuates senescence and reduces fibrosis in cutaneous murine wounds (Jun and Lau, 2017).…”
Section: Senescence In Normal Tissue Repairmentioning
confidence: 95%